(untitled) (Atti del Sodalizio Glottologico Milanese, 2017)
The Milanese dialect has undergone a great deal of change with regard to subject-pronoun organization: after the Middle Ages and until the 17th century, it went through a period where the subject clitic system was far more developed than it is now. Among the various stages that occurred during the course of this evolution, I shall give consideration to the following: i) the ancient subject pronouns in nominative case have become the modern clitic subject pronouns; ii) in the documents dating from the 14th-15th centuries a process begins whereby the order between subject pronoun and pre-verbal negation changes; the first evidence of clitic “a” also appears; iii) in the 17th century, the Milanese dialect had a scl system much richer than now: the presence of scls in the 1st, 2nd, 3rd, and the 6th person (as far as the 4th is concerned, the scl of the 1st person applies; by the end of the 18th century, scls system has acquired a typology similar to that of contemporary Milanese. KEYWORDS: Medieval Romance languages, Tobler-Mussafia Law, Verb Second, Asymmetrical pro-drop, clitic subject pronouns